Střední odborné učiliště, Humpolec - Petřík, Marek; Marek Petřík (České vysoké učení technické v Praze, 2020)
Předmětem mé bakalářské práce je návrh Středního odborného učiliště, které je součástí České zemědělské akademie v Humpolci. Parcela je vymezena ulicemi Hradská a Příčná a okolní zástavbou. Budova je navržena jako solitérní objekt s 2 nadzemními a 1 podzemním podlažím. Budova respektuje uliční profil a doplňuje nároží náměstí.

The subject of my bachelor thesis is a design for the secondary vocational school that is a part of the Czech Academy of Agriculture in Humpolec. The site is demarcated by Hradská and Příčná Streets and the surrounding buildings. The building is designed as a solitaire house with 2 above-ground floors and 1 underground floor. The building respects the profile of the streets and completes a corner of the town square.
Vocational School
Keywords: škola; učiliště; truhlář; tesař; Humpolec; school; vocational school; joiner; carpenter; Humpolec